Fenomena tentang Pengetahuan, Ketersediaan Fasilitas (Availabilitas), dan Dukungan Istri Terkait dengan Perilaku Pria dalam Ber-KB Di Wilayak KerjaPuskesmas Ciruas, Kabupaten Serang Tahun 2019 - Husnul Khotimah (Faletehan Health Journal, 2020)
Family Planning Program is one of the ways that can be taken by the government in overcoming population problems. Efforts to reduce birth rates are not solely the responsibility of wife but also the responsibilities of husband. The participation of men in family planning is a determining factor for the success of the family planning program. This study aims to find out phenomena that occur in society, related to male behavior in family planning at the Work Area of Ciruas Community Health Center, Serang Regency in 2019. The research method uses a phenomenological approach by means of observation and in-depth interviews related to men's knowledge about family planning, availability of facilities and wife support. The data analysis technique used in this study is inductive by analyzing data, reducing data, categorizing data display, and finally making conclusion. The results showed that all informants had less knowledge about male contraception, some informants did not have support from their wives, and some informants assumed that male contraception was not available. Knowledge, wife's support and availability of facilities influence men's behavior in family planning.